Monitoring rock freezing and thawing by novel geoelectrical and acoustic techniques. Issue 12 (10th December 2016) - Murton, Julian B.; Kuras, Oliver; Krautblatter, Michael; Cane, Tim; Tschofen, Dominique; Uhlemann, Sebastian; Schober, Sandra; Watson, Phil
Abstract: Automated monitoring of freeze‐thaw cycles and fracture propagation in mountain rockwalls is needed to provide early warning about rockfall hazards. Conventional geoelectrical methods such as electrical resistivity tomography (ERT) are limited by large and variable ohmic contact resistances, requiring galvanic coupling with metal electrodes inserted into holes drilled into rock, and which can be loosened by rock weathering. We report a novel experimental methodology that combined capacitive resistivity imaging (CRI), ERT, and microseismic event recording to monitor freeze‐thaw of six blocks of hard and soft limestones under conditions simulating an active layer above permafrost and seasonally frozen rock in a nonpermafrost environment. Our results demonstrate that the CRI method is highly sensitive to freeze‐thaw processes; it yields property information equivalent to that obtained with conventional ERT and offers a viable route for nongalvanic long‐term geoelectrical monitoring, extending the benefits of the methodology to soft/hard rock environments. Contact impedances achieved with CRI are less affected by seasonal temperature changes, the aggregate state of the pore water (liquid or frozen), and the presence of low‐porosity rock with high matrix resistivities than those achieved with ERT. Microseismic monitoring has the advantage over acoustic emissions that events were recorded in relevant field distances of meters to decameters from cracking events. For the first time we recorded about 1000 microcracking events and clustered them in four groups according to frequency and waveform. Compared to previous studies, mainly on ice‐cracking in glaciers, the groups are attributed to single‐ or multiple‐stage cracking events such as crack coalescence. Plain Language Summary: Repeated freezing and thawing of steep mountainsides gradually breaks up the bedrock and can make it vulnerable to failure and collapse. To minimize such mountain hazards on people and infrastructure, automatic monitoring of freeze‐thaw and rock cracking is needed. Here we report a new method of monitoring that relies on geophysical techniques that measure the electrical properties of the rock and record tiny rock cracking events. We tested this methodology experimentally in the Permafrost Laboratory at the University of Sussex and provided a new proof‐of‐concept technique that allows us to place sensors onto the rock surface rather than drill them into bedrock, which is often problematic. The new (surface) technique worked better than the existing (drill) technique, and tiny crack events were successfully recorded. Now that our new methodology has been successfully applied under laboratory conditions, it holds promise for installing a similar one under natural field conditions, for example above ski slopes, roads or railways in the European Alps. As the permafrost in such areas warms and thaws, rockfalls and slides are likely to become increasingly important in coming decades, highlighting the growing need for mountain monitoring. Key Points: Capacitive resistivity imaging (CRI) measures freezing and thawing in limestone Microseismic events with characteristics typical of cracking of rock bridges were detected during frost weathering experiments CRI and microseismic techniques offer a viable route for long‐term monitoring of freeze‐thaw and fracture in mountain rockwalls